Non‐linear electrical conductivity of ethylene‐propylene‐diene monomer‐based composite dielectrics by tuning inorganic fillers - Tiandong Zhang; Hao Li; Changhai Zhang; Chao Tang; Zhonghua Li; Qingguo Chi (High Voltage, 2023)
Abstract In this study, three kinds of inorganic fillers are chosen and filled into ethylene‐propylene‐diene monomer (EPDM) matrix, including silicon carbide, copper calcium titanate (CCTO), and vanadium dioxide (VO2). The electrical properties of the three modified composites at different temperatures have been systematically studied. The intrinsic conductance behaviours of different inorganic fillers on the direct current conductance and electric breakdown strength of the composite dielectrics are also analysed, and the possible mechanism for non‐linear conductivity is revealed. The electrical conductivity increases with the increase of fillers content, where 30 wt.% CCTO/EPDM composite dielectric has a high non‐linear coefficient of 5.71. The increase in temperature can further increase the conductivity of the composites, accompanying a lower breakdown strength. When the temperature rises to 70°C, the VO2/EPDM composite has a higher conductivity, but the electric breakdown strength degrades seriously. The simulation results show that the composites with non‐linear electrical conductivity characteristics can effectively uniform the electric field and solve the problem of electric field concentration at the root of the stress cone, which is beneficial to improving the safe operation of the cable accessories.